Prosthetic Rehabilitation on Edentulous Patients with Microstomia: About Three Cases - Oumaima Tayari; Jamila Jaouadi; Safa Jemli; Hela Haloui; Ali Ben Rahma (Case Reports in Dentistry)
Limited oral opening is an acquired or congenital abnormal condition that compromises patient esthetics, nutrition, and quality of life. In addition, it may hinder conventional prosthetic procedures of edentulous patients, make it challenging, and present difficulties at all its stages. This clinical report presents different clinical treatment options suitable to be chosen by the prosthodontic carer in the case of reduced oral aperture.